REDISEÑO DEL SISTEMA ELÉCTRICO EN EL EDIFICIO “PAÑALERA ROSARITO” - Castillo Mestanza, Alfredo Fernando (2017)
Electrical installations are classified depending on the voltage level in high voltage, medium voltage and low voltage. In low voltage it is subdivided into two applications which are residential or industrial installations. (Ceduvit, (2014) Residential electrical installations Ceduvit, p.65) In the same way the electrical installations represent a risk for the human being, reason why it is necessary to provide the maximum security to those who are in charge of transporting, distributing and operating with the electric energy, in order to safeguard the physical integrity as well as the goods materials. For this reason residential and industrial electrical installations are executed according to technical and normative standards in order to contribute to energy savings, efficiency in the consumption, efficiency in the delivery of energy and avoiding accidents increasing business productivity. (wordpress. (09 of 04 of 2017) Retrieved from https://escomexico.wordpress.com/2013/06/13/importancia-de-una-buena-instalacion-electrica) The main objective of this project is to redesign the electrical system of a building with a high energy demand which has problems due to losses due to wear and generate more expense in the worksheet. This work also aims to evaluate the current conditions of existing electrical installations in the building "Pañalera Rosarito", to do the analysis and design of new circuits that should be implemented if necessary. Due to the increased load that the "Pañalera Rosarito" wishes to implement, it is necessary to review and improve the existing electrical installations so that the future installations to supply the demand for these increases and guarantee the correct operation of the same in the different areas that will be used.